Mother's Knowledge and Attitude Correlated with Nutritional Status of Children - Hardianty, Angraeni; Anwar; Wahyuni, Andi (Bantayang Omni Cendekia, 2024)
Background: Nutritional status is a health status that is produced by the balance between nutritional needs and inputs and for growth and development. Nutritional problems have also become a problem in South Sulawesi, especially in Makassar. Objective: This study aimed to determine the relationship between mothers' knowledge and attitudes with nutritional status of children in the working area of Batua Health Center Makassar. Methods: This was an observational study with a cross-sectional approach. The population was 116 children aged 1-5 years. The sampling technique used purposive sampling with a sample of 54 children. This study used questionnaires and observation sheet to collect data. Results: The Chi-square test showed a significance value of X2 calculation (18.917) > X2 table (3.841) and, which means that there was a correlation between mother's knowledge and children's nutritional status. Also, the Chi-square test showed significance value of X2 calculation (14.464) > X2 table (3.841), indicating that there was a correlation between mother's attitude and children's nutritional status. Conclusion: There is a relationship between mothers' knowledge and attitudes with nutritional status of children. It is recommended to parents, especially mothers, to pay more attention to children's food intake and get used to children to eat regularly and provide nutritious food every day so that children's nutritional intake can be met.